The Vigor and Viability Seed Testing of Three Tobacco Varieties on Various Seed Germination Media - Taufiq Hidayat RS; Aprilia Ridhawati (Universitas Sembilanbelas November Kolaka, 2020)
Seed viability is one of the most important physiological quality benchmarks of seeds. The use of appropriate germination media can affect the results of seed viability testing. This study aims to determine the optimal germination media in tobacco seed viability testing. This research was conducted at the Seed Laboratory of the Indonesian Sweetener and Fiber Crops Research Institute, Malang in January - March 2019. The research method used a two-factorial randomized block design (RAK). The first factor is tobacco seed varieties consisting of Kasturi in 2007, Bojonegoro in 2012 and Kemloko in 2014. The second factor is the seed germination media consisting of straw paper, cotton, towel tissue, paperboard and newspaper. The results showed that the Kemloko variety of tobacco seeds germinated in the towel tissue had the best seed vigor and viability percentage. Seed germination media with paperboard, towel tissue and straw paper can be used to test the viability of tobacco seeds because they have a percentage of simultaneous growth, percentage of the growth speed, percentage of germination, percentage of the growth potential maximum and normal seedling dry weight which are equally well